Continuous nursing symptom management in cancer chemotherapy patients using deep learning - Jie Zhang; Xiao-nan lv; Mei Wang; Jun Zhang; Feng Qi (Scientific Reports)
Abstract To assess the efficacy of a deep learning platform for managing symptoms in chemotherapy patients, aiming to enhance their quality of life. A non-randomized controlled trial was conducted from September 2022 to March 2024, involving 144 chemotherapy patients divided into intervention (n = 72) and control (n = 72) groups. The intervention group received the deep learning platform, whereas the control group received standard care. Anxiety, depression, and quality of life were evaluated using the SAS, SDS, and QOL scores at baseline and after 6 months. Initial non-significant differences in SAS, SDS, and QOL scores between groups were observed. After intervention, significant improvements were noted in the intervention group for SAS, SDS, and various QOL aspects (P < 0.05). The platform received a high satisfaction score of 4.93 ± 0.13. The deep learning platform significantly reduced anxiety and depression and improved QOL in chemotherapy patients, demonstrating high patient satisfaction and potential for clinical application. Clinical trial registration: The trial was registered in clinical trials.gov with the registration number ChiCTR2400093540. The first registration date was 06/12/2024.